(3QSGdI aj GdJhMjOs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdGfSGf GWhGQkG faSkG hQhMkG hLSekG hLYd Pdc GdJQcjH GdYLjH Ydi NRGFf GSQGQg WdSekG s
(3BNQgG (B:s
(3aGfaPhG dJNQWhG ai Sdc GdGQhGM GdedchJjI hGdfahS GdLHQhJjI Gh JUdhG Edi GdMVQI GdEdgjI dGJfaPhf EdG HSdWGf Gi HMLI Hjfg gi GdJhMjO hGdJLQjO hGdJaQjO HGdYde hGdYed hGdZfGA ai Gddg JYGdi JeJ GdQSGdI dGHf ceGd HGTG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJhMjO hGdedd hGdfMds